2009
DOI: 10.1007/s11552-009-9195-6
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Outcomes with the Use of Decellularized Nerve Allograft for Repair of Sensory Defects within the Hand

Abstract: Nerve conduits have become an established option for repair of sensory deficits of up to 2 cm. More recently, decellularized nerve allograft has also been advocated as an option for nerve repair; however, no clinical studies have examined its efficacy for the treatment of sensory nerve defects. The aim of this study was to examine our early experience with the use of decellularized nerve allograft for repair of segmental nerve defects within the hand and fingers. From July 2007 to March 2008, seven patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
148
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(155 citation statements)
references
References 30 publications
(48 reference statements)
3
148
0
4
Order By: Relevance
“…Several studies have reported that decellularized allografts have consistently performed better than other commercially available grafts, which is most likely due to these grafts possessing the necessary architecture and guidance cues from nerve ECM components to promote axon regeneration (Karabekmez et al, 2009;Kehoe et al, 2012;Whitlock et al, 2009). A majority of protocols that decellularize nerve grafts are based on those developed by Sondell et al (Sondell et al, 1998) and Hudson et al(Hudson et al, 2004b) that predominantly use chemical decellularization agents.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that decellularized allografts have consistently performed better than other commercially available grafts, which is most likely due to these grafts possessing the necessary architecture and guidance cues from nerve ECM components to promote axon regeneration (Karabekmez et al, 2009;Kehoe et al, 2012;Whitlock et al, 2009). A majority of protocols that decellularize nerve grafts are based on those developed by Sondell et al (Sondell et al, 1998) and Hudson et al(Hudson et al, 2004b) that predominantly use chemical decellularization agents.…”
Section: Introductionmentioning
confidence: 99%
“…(10,11,12) Several authors have reported success with processed nerve allografts. (1,2,13,14) One such allograft is the AvanceÂŽ processed nerve graft (AxoGen, Inc., Alachua, FL). It consists of human nerve that has been decellularized, gamma irradiated, and subjected to enzymatic degradation of chondroitin sulfate proteoglycans with chondroitinase.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the allograft is rendered nonimmunogenic while its 3-dimensional structure is maintained. (14,15) Animal studies have shown this material to mimic autografts in macrostructure, 3-dimensional microstructural scaffolding, and protein composition. Theoretically, these qualities render 6 allograft an effective material to span peripheral nerve defects.…”
Section: Introductionmentioning
confidence: 99%
“…Although initial reports focused on short gap repairs, 5,18,26 several substrates have been studied for their potential to heal large gap defects when supplemented with AGCs, including purified SCs. 1,6,7,9,11,12,16,17,27,28,34,37,38,[40][41][42]44 Berrocal et al demonstrated that adding autologous SCs suspended in serum to AGCs significantly enhanced the ability to bridge larger gap distances in sciatic nerve repair in rats.…”
Section: Discussionmentioning
confidence: 99%